Engaging learning with Augmented Reality for primary school science education - Nur Amira Baiduri, Azlan (2019)
Augmented Reality (AR) is one of the visualization technologies that gradually gaining considerable attention in every field, especially in education area. AR have been applying in education field to create a unique learning experience. In early age of education, primary school students have trouble grasping and understanding the abstract science concept. By bringing the AR into the classroom, AR can serve as an effective tool to gain understanding since AR offer rich media learning. Therefore, the purpose of this project is to design and develop a Science AR application for primary school students. Besides displaying each process upon presentation of its corresponding marker, students can visualize the concept of science in process of learning. Three existing application of AR in the field of education has been review to produce a better version of application. ADDIE model has been chosen in development of this application. There were five phases involved in the model to make sure that the designing and developing of the application has achieves the proposed objective. The application was evaluated by the teacher and primary school students to investigate its effectiveness and user perception toward the application. The result showed that students give positive feedback and they agree this application can improved their understanding in science subject.